Improving Student's Critical Thinking Ability Using Argument-Drivent Inquiry Approach in Thermochemistry - Purwandari, Intan Diah; Muntholib; Anugrah Ricky Wijaya (Universitas Negeri Surabaya, 2023)
This study aimed to investigate the impact of the Argument-Driven Inquiry instruction (ADI-Based Instruction) in thermochemistry on students' critical thinking skills. This study applied the one group pretest-posttest type of pre-experiment design. The subjects of this study were 71 eleven grade students of Public Senior High School of Ambulu Jember on academic year of 2022/2023. The instrument, namely the critical thinking ability test on thermochemistry, was developed by the researchers based on Ennis' critical thinking ability framework. This test consists of 10 valid items with a Cronbach's Alpha reliability of 0.782. The results showed that thermochemistry instruction carried out using ADI instructional model improve students' critical thinking skills with an N-gain of 0.731 (high category) and Cohen's d-effect size of 1.023 (large effect category) with an intermediate reliability of 0.619 (good categories). These results indicate that ADI-based instruction on thermochemistry can improve students' critical thinking skills. The implication of this study is that ADI-based instruction can be applied to other subjects who have the same characteristics of thermochemistry, namely having contextual, factual, conceptual, procedural, and metacognitive knowledge.